2016
DOI: 10.31248/jasvm2016.008
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of management practices of Tswana chickens at North East District of Botswana

Abstract: The objective of this study was to document management practices, economic benefits and challenges in indigenous Tswana chicken production in Jackalas No.2, Moroka and Tsamaya villages of North East District of Botswana. Structured questionnaire, oral interviews and field observations were used in collecting data from 50 farmers from the three villages for six successive weeks (i.e., November to December, 2015). All data generated were subjected to descriptive statistics using frequencies, percentages and mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The mortality of chicken was observed as major constraint to backyard chicken management at village levels in Ethiopia, where efforts should be geared towards the improvement of health and management practices to improve rural backyard chicken production (Weyuma et al, 2015). Moreki et al (2016) reported that in order to increase the benefits of rearing indigenous (Tswana) chickens, the farmers should be trained in general poultry husbandry management and also be encouraged to form associations to assist them in marketing chickens, because Tswana chickens play an important role in food security at household level of the rural populace in Botswana. In Nigeria, Odemero & Oghenesuvwe (2016) recorded a mortality rate of 12% and indicated that litter replacement frequency, stocking density (0.87), available biosecurity infrastructure and routine cleanliness were significant biosecurity factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mortality of chicken was observed as major constraint to backyard chicken management at village levels in Ethiopia, where efforts should be geared towards the improvement of health and management practices to improve rural backyard chicken production (Weyuma et al, 2015). Moreki et al (2016) reported that in order to increase the benefits of rearing indigenous (Tswana) chickens, the farmers should be trained in general poultry husbandry management and also be encouraged to form associations to assist them in marketing chickens, because Tswana chickens play an important role in food security at household level of the rural populace in Botswana. In Nigeria, Odemero & Oghenesuvwe (2016) recorded a mortality rate of 12% and indicated that litter replacement frequency, stocking density (0.87), available biosecurity infrastructure and routine cleanliness were significant biosecurity factors.…”
Section: Discussionmentioning
confidence: 99%
“…In several recent studies, however, biosecurity and other preventive measures (Akpabio et al, 2014), management practices coupled with small feed supplement (Getu & Birhan, 2014), improved chicken and market facilities at village levels (Tsegaye et al, 2014), improvement of health of the rural backyard chicken production (Weyuma et al, 2015), training in poultry husbandry management and facilities for marketing chickens (Moreki et al, 2016) and routine cleanliness and regular workshops on biosecurity management practices organized by the government and relevant agencies (Odemero & Oghenesuvwe, 2016) have been implicated.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some processors also have slaughterhouses to slaughter indigenous chickens. Slaughtered chickens are packed and processed to sell to frozen market [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]34].…”
Section: Literature Review 21 Indigenous Chicken Value Chainmentioning
confidence: 99%
“…Indigenous chicken farming in Nigeria provides indirect and direct employment to almost 20 million people and the total contribution of the poultry industry in Nigeria's GDP is about 10%. Additionally, in the Caribbeans region and Haiti 95% of the rural households rear indigenous chicken to earn livelihood [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Farmers have specialized in duck farming businesses such as hatchery businesses (producing ducklings / DOD), rearing businesses (producing pre-laying ducks), fattening male ducks, producing consumption eggs, and hatching eggs. Farmers' livestock businesses have proven to be a source of income, poverty alleviation, food security, and organic fertilizer [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%